Институциональные факторы стабильности слабоинтегрированного украинского общества - Резник, А. (Социология: теория, методы, маркетинг, 2005)
The article deals with stability of the Ukrainian society phenomenon. The author has suggested methodological aspects for study of stability phenomenon in insufficently integrated society. It has been revealed that stability factors ar:e institutional features of regional elites formation, no ethnic stratification, and spreading confidence that interethnic conflicts will not occur in Ukraine. The demoralization of Ukrainian population caused the anomie of values contributed to distancing from any actions (including separatist ones) that are destructive to sovereignty.